Primary pulmonary adenocarcinoma in a 16-year-old boy – a five-year follow-up - Måreng, Ane Stillits (Eur Clin Respir J, 2016)
Primary pulmonary adenocarcinoma in children or adolescents is a rare disease, and as such, there are no randomised studies on lung cancer for this age group. Treatment choice is extrapolated from studies in adults (mean age of participants: 60 years). We present the 5-year follow-up of a 16-year-old boy who presented with metastatic primary pulmonary adenocarcinoma (T3N3M1a) and was treated aggressively, including radiation therapy for local and distant recurrence. He had complete remission, had completed his education, was employed full-time, and suffered only from mild side effects to treatment.